(untitled) (Research, Society and Development, 2020)
The estimated global prevalence of patients on chronic dialysis has increased over the years, with some countries where the lack of this therapy becomes more frequent. In Brazil, prevalence rates have progressively increased in all regions, which has a major impact on public health and quality of life for patients. Thus, it is necessary to have nurses in multidisciplinary actions linked to hemodialysis patients, encompassing educational, technical and managerial proposals, favoring greater knowledge on the subject. The objective is to know the role of nurses in the care of hemodialysis patients. It is an integrative review with six articles selected from the LILACS and SciELO databases between 2010 and 2020. After reading, analyzing and interpreting the data, the publications showed different challenges faced by nurses in the care of dialysis patients, his role being indispensable in guiding the disease and treatment. Knowing the barriers related to the adequate treatment of physical and psychosocial illness, among other demands in the social context, can be an important tool in the search for ways to offer more quality assistance to this population.